2016
DOI: 10.1128/aac.00933-16
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Dissemination of a Mobilizable Plasmid Harboring bla IMP-19 and the Possibility of Horizontal Gene Transfer in a Single Patient

Abstract: dCarbapenemase-producing Gram-negative bacilli have been a global concern over the past 2 decades because these organisms can cause severe infections with high mortality rates. Carbapenemase genes are often carried by mobile genetic elements, and resistance plasmids can be transferred through conjugation. We conducted whole-genome sequencing (WGS) to demonstrate that the same plasmid harboring a metallo-␤-lactamase gene was detected in two different species isolated from a single patient. Metallo-␤-lactamase-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
(40 reference statements)
0
9
1
Order By: Relevance
“…They often contain genes responsible for a wide range of functions, including virulence, antibiotic resistance, and symbiosis ( 3 5 ). Conjugative plasmids and ICEs can often transfer between different bacterial species and genera and mobilize genomic islands or plasmids that are otherwise not self-transmissible, granting these elements an extensive role in bacterial evolution ( 6 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…They often contain genes responsible for a wide range of functions, including virulence, antibiotic resistance, and symbiosis ( 3 5 ). Conjugative plasmids and ICEs can often transfer between different bacterial species and genera and mobilize genomic islands or plasmids that are otherwise not self-transmissible, granting these elements an extensive role in bacterial evolution ( 6 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…This plasmid belongs to the IncX3 group which was reported to be the most common Inc type plasmid that harbored bla NDM gene in China. 22 Nucleotide BLAST revealed that pR15_NDM-5 was highly similar to pNDM-MGR194 (99% identity and 100% coverage). 23 Furthermore, genetic environment characterization revealed a structure of IS26-dsbC-trpF-ble MBL -bla NDM-5 -IS5 in both plasmids ( Figure 1B).…”
mentioning
confidence: 99%
“… Escherichia coli strain ME8067 (strain WD8014) is a laboratory E. coli strain that cannot ferment galactose due to its lack of UDP glucose pyrophosphorylase activity ( 1 ). This strain has been used for conjugation experiments as a recipient strain ( 2 4 ) because it is negative for fertility factors and is resistant to sodium azide. Recent advances in sequencing technology have enabled the sequencing of transconjugants, which contribute to a comprehensive understanding of transferable elements.…”
Section: Genome Announcementmentioning
confidence: 99%